EXPLORING TEACHER WORKLOAD CHALLENGES IN THE MERDEKA CURRICULUM ERA: A NASA-TLX-BASED ANALYSIS OF ADMINISTRATIVE TASK IMPACT ON PERFORMANCE AND WELL-BEING - Norman, Efrita (PROCEEDING OF INTERNATIONAL CONFERENCE ON EDUCATION, SOCIETY AND HUMANITY, 2024)
The research explores the challenges of teacher workload in the context of the Merdeka Curriculum, mainly focusing on the impact of administrative tasks on teacher performance and well-being. In recent years, implementing the Merdeka Curriculum has significantly altered the teaching and administrative duties structure, creating new challenges for educators. This study examines how administrative workload affects teachers' ability to perform effectively in the classroom and influences their overall well-being. A NASA-TLX-based analysis assessed the cognitive, physical, and emotional demands placed on teachers due to administrative tasks. Data was collected through surveys and interviews with teachers across various schools implementing the Merdeka Curriculum. The findings indicate that administrative tasks are a significant source of stress, contributing to burnout and reduced teaching efficacy. Teachers reported that increased administrative workload negatively impacted their ability to focus on instructional quality and student engagement. The study concludes that while administrative tasks are necessary, they need to be better balanced to support teachers' performance and well-being. This research contributes to understanding the critical factors influencing teacher satisfaction and productivity in the Merdeka Curriculum era, highlighting the importance of addressing workload distribution to enhance educational outcomes and support teachers' mental health.